Keep Faith in Yourself! A Pilot Study on the Relevance of Specific Self-Efficacy for Modifying Sexual Interest in Children Among Men With a Risk to Sexually Abuse Children. Issue 6 (18th August 2018) - Tozdan, Safiye; Kalt, Anna; Keller, Livia B.; Briken, Peer
ABSTRACT: Among 26 pedophilic/hebephilic men, we investigated (1) the relationship between "specific self-efficacy for modifying a sexual interest in children" (SSIC) and actual sexual interest in children and (2) whether changes in SSIC are associated with changes in sexual interest in children. Results showed that the more clients believe they are able to influence their sexual interest in children, the less strong they perceive their sexual interest in children to be. Furthermore, an increase in SSIC is associated with a decrease in sexual interest in children. We suggest avoiding generalized statements about the immutability of sexual interest in children.